“Who’s the next einsteingen?”: Evaluating a gamified Project-Based Learning model for TPACK development and user satisfaction in physics teacher preparation - Yudi Guntara; Sohibatul Rizqiah; Aden Yusril Sasmita; Yoni Yoni; Bunga Kusuma Putri; Febri Sahara; Salwa Nurfitriandini; Muhammad Rayhan Dwi Ernanda (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2026)
Physics teacher education is faced with the challenge of equipping prospective teachers with TPACK competencies and skills to design learning media that are relevant to Generation Z. This study aims to evaluate the effectiveness of gamification-integrated Project-Based Learning (PBL) programs through the production of educational game show media "Who's the Next Einsteingen?" or WtNE. This study uses a program evaluation approach with the CIPP and Kirkpatrick evaluation models. Participants consisted of 50 prospective physics teacher students as project makers and 40 students as audiences. Data was collected through project performance appraisal instruments and Likert-scale user response questionnaires, which were then analyzed using descriptive statistics. The results of the performance evaluation showed that the majority of project makers (66%) obtained a final grade of “A”, which indicates successful mastery of pedagogical and technical competencies. In addition, product evaluations show that audiences respond very positively, with gamification attractiveness indicators achieving the highest approval (87.8%). It can be concluded that the WtNE gamification-based PBL model is effective as a holistic learning ecosystem that is able to develop the competencies of prospective physics teachers while producing media that is in great demand by target users.